Understanding self‐perception accuracy: Implications for human resource management - Yammarino, Francis J.; Atwater, Leanne E. (Human Resource Management, 1993)
AbstractA conceptual model of self‐perception accuracy is developed, and its managerial and research implications for human resources management are discussed. The model is based on a series of studies designed to enhance understanding of self–other agreement and the accuracy of self‐perception. Accuracy is defined as the degree of agreement between self‐and other‐evaluations/ratings. In this framework, “other‐ratings” may be provided by subordinates, peers, superiors, or customers/clients, so that self–other agreement includes the entire 360‐degree range of feedback sources available to a focal individual. The evaluations/ratings may concern any of the key areas in personnel and human resource management such as training needs assessment, performance appraisal, or leadership behaviors. The model posits enhanced individual and organizational outcomes when self‐perception is accurate and diminished or mixed outcomes when self‐perception is inflated or deflated, respectively. © 1993 by John Wiley & Sons, Inc.